The Value Relevance of Accounting Variables and Analysts’ Forecasts: The Case of Biotechnology Firms - LIM, Chee Yeow (Institutional Knowledge at Singapore Management University, 2007)
This paper seeks to address the value relevance of summary accounting measures and fundamental income statement variables in the market valuation of biotech firms. A biotech firm's stock price was related to its underlying financial accounting variables. Using the Ohlson model, the linear function of book value and earnings was employed, and the basic model was augmented with additional accounting variables. These accounting variables may provide information relevant for forming an approximation on the present value of expected future abnormal earnings. Results show non-linearities in the pricing of accounting variables Both book value and earnings are value relevant, but positive earnings are positively priced while negative earnings are negatively priced. R&D spending and selling, general and administrative expenses are also priced as assets for loss-reporting firms, and as expenses for profit-reporting observations. Including analysts' forecasts of future earnings and long-term growth rate in the model results in an insignificant increase in the explanatory power of the regressions. Future research could attempt to examine the role of non-financial variables which can proxy for the soft variables and intangibles like strategic alliances and product pipeline.